Assessment of Seventh Grade Students’ Capacity of Logical Thinking (Jurnal Pendidikan IPA Indonesia, 2019)
The objective of this research was to quantify the logical thinking capacity ofseventh grade students in Tuban, East Java, Indonesia. This research was conducting using the quantitative descriptive method and 119 students in the seventh grade of secondary school in Tuban during the Academic Year 2016/2017. The data was collected by using Logical Thinking Test (LTT) which comprises of six different kind of reasonings; namely conservational reasoning, proportional reasoning, controlling variables, combinatorial reasoning, probabilistic reasoning, and correlational reasoning (source). Based on LTT, scores are categorized into three levels; concrete operational levels, transitional levels, and formal operational levels (source). The results of the research display that (88.21%) of the seventh grade are classified at the concrete operational level, (10.08%) at the transitional level, and (1.68%) at the formal operational level. After conducting this research, teachers are now able to design teaching tactics and have a better understanding of secondary school student’s cognitive development and behavior